A strategic multi-step PMU allocation based on direct monitoring for smart grid (SG) implementation - Maji, Tapas Kumar; Acharjee, P. (2017 IEEE Transportation Electrification Conference (ITEC-India), 2017)
The utilization of phasor measurement unit (PMU) is highly recognized in modern power industry for its smart measurement capability. To implement a smart transmission network, PMU should be allocated at all buses but for large power systems, PMU allocation at all buses is a matter of huge investment and it should be conducted in certain number of steps. In this paper, an effective and practical multi-step PMU allocation strategy is proposed for IEEE 30-bus test system. In, the proposed strategy, the multi-step PMU allocation is framed in such a way that the important and preferred buses will be directly monitored during the initial and intermediate steps. In this paper, several strategies such as optimal PMU allocation (OPA) for full observability, important and critical bus preferences are taken into account. An efficient binary crow search algorithm (BCSA) is developed to solve the OPA problem and the developed algorithm is compared with other metaheuristic algorithms to show its efficiency.